Continuidade. Ruptura - Ana Teresa Teixeira Espinheira Rio (2015)
This dissertation focuses on the theme of building rehabilitation, the different possible approaches and changes to give a new life to an existing building. Within the Rehabilitation theme, there is always a constant confrontation between the creation and/or maintenance of constructive elements and the possible discontinuity with the past; there is a confrontation between Continuity and Rupture. In this essay is discussed the meaning of heritage, the history that buildings carry a long time, the stories that they hold between their walls and the meaning they had once in other lives and past experiences. From the generality of this theme, emerges a real problematic: the rehabilitation of a house located in Marco de Canavezes. This building, which is currently unoccupied, has over fifty years of existence and reflects in many of its elements the characteristics of different periods in time. The problem, along with the rehabilitation of the house, is it's adaptation to new needs, finding a balance between which elements to keep and what changes to make. In order to understand how to rehabilitate this House, it was necessary to understand its characteristics and references. From physical factors such as light or the building's own stereotomy, to intangible factors such as the house's temporal organization (built in several phases), to the detail of the chimney - referenced in the "Inquérito à Arquitectura Popular" - and also the insertion of the House in a rural context, with clear economic implications on its construction. These and other factors affect the process of often choosing between contradictory options, to come up with a final solution. From a more practical point of view, it was necessary to revisit texts and reference works in order to find a reasonable response for each problematic. For example, the stairs with double height, developed as the solution that better organized the upper floor. As on the other hand, the preservation of the chimney no longer made sense, as it doesn't respond to its original function, therefore it was removed. The final results can't be taken as the only possible solution. Rehabilitation can't be seen as an absolute choice between Continuity and Rupture, but instead as a continuum of solutions where a balance must be found between the pre-existing conditions and the customer requirements, while meeting the value that architecture can add to the life of a building and its inhabitants.